Analisis Perbandingan Return on Assets BRI Syariah Sebelum dan Setelah Merger - Egi Afrillia; Nana Diana (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
Merger is a cooperation contract to merge companies into one company. This study was conducted to determine whether there was a significant difference in profitability values before and after the merger at BRI Syariah. The data obtained is secondary data from BRI Syariah website and the Indonesia Stock Exchange (idx). ROA experienced ups and downs before the merger (2015-2020) and tends to increase after the merger on February 1, 2021. The data has been normally distributed, so the comparative analysis was carried out using the Paired Samples Test, the Paired Samples Statistics table shows that the average value The average return on assets before the merger is 0.003589 and after the merger is 0.008305, which also shows that there are differences in ROA values. So in this study H0 is rejected and Ha is accepted, there is a significant change in the profitability value of Return On Assets before and after the merger, where after 3 quarters of the merger, the profitability of Bank Syariah Indonesia has increased significantly compared to before the merger.